The Effect of Presentation and Transparency of Financial Reports on Accountability of Financial Management - Berliana, Deta; Setiawan, Ade Budi; Jamaludin Aziz, Ayi (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the effect of financial statement presentation and transparency on the accountability of financial management in Regional Apparatus Organizations (OPD) through accessibility in Bogor City. The study population includes five OPDs spread across Bogor City. Using the purposive sampling method, the study involved 52 respondents. The research instrument utilized a questionnaire to collect data from the respondents. The analysis results indicate that the presentation of financial statements alone does not have a significant effect on the accountability of financial management in OPDs. However, when the presentation of financial statements and transparency are combined, they have a significant effect on the accountability of financial management through accessibility in Bogor City. This suggests that a combination of good presentation and high transparency in financial statements is necessary to enhance accountability in the financial management of OPDs. The study emphasizes the importance of these two aspects in ensuring accountable financial management within the government.